2010
DOI: 10.1111/j.1755-3768.2008.01446.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anterior segment parameter changes using the Pentacam after uneventful phacoemulsification

Abstract: ABSTRACT.Purpose: This study set out to evaluate the influences of uneventful phacoemulsification on the anterior segment parameters obtained with the Pentacam rotating Scheimpflug camera and intraocular pressure (IOP). Methods: A total of 42 eyes of 34 patients (26 men, eight women) were evaluated preoperatively, and at 1, 3 and 6 months postoperatively with the Pentacam. Intraocular pressure was measured with the Goldmann applanation tonometer. The non-parametric paired t-test was used to compare preoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 33 publications
6
53
2
3
Order By: Relevance
“…However, this was different to what was stated by Doganay et al [23], who found no difference between preoperative and postoperative CCT. They found the mean CCT measurements were 534 ± 34 µm preoperatively and 528 ± 35 µm, 528 ± 36 µm and 538 ± 37 µm at 1, 3 and 6 months postoperatively, respectively.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…However, this was different to what was stated by Doganay et al [23], who found no difference between preoperative and postoperative CCT. They found the mean CCT measurements were 534 ± 34 µm preoperatively and 528 ± 35 µm, 528 ± 36 µm and 538 ± 37 µm at 1, 3 and 6 months postoperatively, respectively.…”
Section: Discussioncontrasting
confidence: 56%
“…In their study, before surgery, the mean anterior chamber angle widths were 23.21 ± 6.70° in the nasal quadrant and 24.89 ± 7.66° in the temporal quadrant which increased significantly to 35.16 ± 4.65° in the nasal quadrant (p=0.001) and 36.03 ± 4.86° in the temporal quadrant (p=0.001). Also, Doganay et al [23], found the mean anterior chamber angle (ACA) measurements were 33 ± 6° preoperatively changed to 42 ± 7°, 44 ± 7° and 43 ± 6° at 1, 3 and 6 months postoperatively, respectively. The differences between pre and postoperative ACA measurements were statistically significant (p<0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurements of ACD did not change significantly at the 1-3-and 6-month examinations postoperatively, which was in accordance with that has been reported by Doganay et al 13 That means the values of anterior chamber depth remained stable after one month of phacoemulsification. There were no significant changes of corneal curvature measurements by pentacam preoperatively and over the 6 months postoperatively.…”
Section: Discussionsupporting
confidence: 92%
“…This measurement provides essential information about the angle anatomy necessary to diagnose the type of glaucoma and to assess the risk for developing angle-closure glaucoma [1]. Likewise, IA is also a parameter to consider when planning refractive surgery with implantation of an angle-supported phakic intraocular lens [2].…”
Section: Introductionmentioning
confidence: 99%